THE RELATIONSHIP INTENSITY OF USE OF INTERNET WITH SOCIAL IMPACT ADOLESCENTS IN STUDENTS / CLASS VIII SMP 02 JASINGA IN 2018: HUBUNGAN INTENSITAS PENGGUNAAN INTERNET DENGAN DAMPAK SOSIAL REMAJA PADA SISWA/I KELAS VIII SMP 02 JASINGA TAHUN 2018 - Elpinaria Girsang, Elpinaria; Iis Lestari, Iis (Wijaya Husada, 2018)
Background: Adolescents according to World Health Organitation (WHO) (2013) are age groups10-19 years. Adolescence consists of three obvious subfases, namely early adolescence (ages 11 to14 years), middle adolescence (ages 15 to 17 years) and late adolescence (ages 18 to 20 years). Inadolescents, gradually, physical, mental, mental, psychological, and social and emotionalmaturity will arise. (2)Research Objective: to find out the correlation between the intensity of internet usage and thesocial impact of adolescent students in SMP 02 Jasinga Tahun 2018.Research Methods: This study is an analytical survey with a cross sectional approach. Thepopulation of this study was 30 students in SMP 02 Jasinga with a total sampling technique.Research Results: The results of this study can be seen that from 30 respondents, 14 respondents(46.7%) students / i the intensity of internet use is not often positive as many as 4 respondents andthe negative ones as many as 14 respondents. And the intensity of internet usage is often positiveas many as 9 respondents then the negative ones are 3 respondents with a value of p Value 0.004.Conclusion: There is a correlation between the intensity of internet usage and the social impact ofadolescents in SMP 02 Jasinga Tahun 2018.